2013
DOI: 10.1371/journal.pone.0071169
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Alcohol Availability Predicts First-Time Drunk Driving, but Not Repeat Offending

Abstract: Alcohol availability has been linked to drunk driving, but research has not examined whether this relationship is the same for first-time and repeat offenses. We examined the relationship between the business hours of alcohol outlets licensed to serve alcohol for on-premises consumption and misdemeanor-level (first offense) and felony-level drunk driving (repeat offense) charges in New York State in 2009. Longer outlet business hours were associated with more misdemeanor drunk driving charges, but were not ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This finding seems to resonate with an observation made repeatedly in the previous literature: that alcohol policy environments had stronger associations with lighter drinking patterns (e.g., "any drinking") than with heavier drinking patterns (e.g., "binge drinking", Bendtsen et al, 2014;Gilligan et al, 2012;Paschall et al, 2009). Furthermore, there is strong resemblance to a finding from an ecological study of counties in New York State, reported by Schofield and Denson (2013). These investigators found that longer outlet business hours -a result of corresponding alcohol policies -were associated with first-time drunk-driving, but not with repeat drunk driving.…”
Section: Relationships Tapered Offsupporting
confidence: 86%
“…This finding seems to resonate with an observation made repeatedly in the previous literature: that alcohol policy environments had stronger associations with lighter drinking patterns (e.g., "any drinking") than with heavier drinking patterns (e.g., "binge drinking", Bendtsen et al, 2014;Gilligan et al, 2012;Paschall et al, 2009). Furthermore, there is strong resemblance to a finding from an ecological study of counties in New York State, reported by Schofield and Denson (2013). These investigators found that longer outlet business hours -a result of corresponding alcohol policies -were associated with first-time drunk-driving, but not with repeat drunk driving.…”
Section: Relationships Tapered Offsupporting
confidence: 86%
“…Previous studies have shown that changes in on-premise closing hours at the local level can affect violence, drunk driving, and disorderly behavior (Duailibi et al, 2007; Kypri, McElduff, & Miller, 2014; Popova et al, 2009; Ragnarsdottir, Kjartansdottir, & Davidsdottir, 2002; Rossow & Norström, 2012; Schofield & Denson, 2013a, 2013b). The present study has added to the sparse knowledge about the processes that underlie such changes.…”
Section: Discussionmentioning
confidence: 99%